2016
DOI: 10.1016/j.cviu.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of local parametric candidates with exemplar-based occlusion handling for optical flow

Abstract: Handling all together large displacements, motion details and occlusions remains an open issue for reliable computation of optical flow in a video sequence. We propose a two-step aggregation paradigm to address this problem. The idea is to supply local motion candidates at every pixel in a first step, and then combine them to determine the global optical flow field in a second step. We exploit local parametric estimations combined with patch correspondences and we experimentally demonstrate that they are suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 76 publications
(176 reference statements)
0
54
0
Order By: Relevance
“…For example, the 8-parameter quadratic model represents rigid motion of a planar surface in perspective projection. The small number of parameters of the affine model and its realistic local assumption make it often considered as the best trade-off between complexity and descriptiveness [27,88,175,193]. The accuracy of local affine motion estimation in appropriate estimation support was experimentally demonstrated in [88].…”
Section: Polynomial Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the 8-parameter quadratic model represents rigid motion of a planar surface in perspective projection. The small number of parameters of the affine model and its realistic local assumption make it often considered as the best trade-off between complexity and descriptiveness [27,88,175,193]. The accuracy of local affine motion estimation in appropriate estimation support was experimentally demonstrated in [88].…”
Section: Polynomial Modelsmentioning
confidence: 99%
“…A smoothness constraint is assumed on n o and n m , either with a local parametric form [188,193] or a global regularization [55,89,142,159,239]. The offset formulation is also used in [10,88], but is associated to a sparsity constraint aiming at retrieving violations due to occlusions. The more general approach of [74] parametrizes intensity changes in terms of Brightness Transfer Function [106], which coefficients are learned from training data.…”
Section: Modeling Intensity Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We integrated our model in a variational framework adapted to small displacements. Other approaches to deal with large displacements and occlusions could be considered in the future [16,23,26]. …”
Section: Conclusion -Perspectivesmentioning
confidence: 99%
“…The reason is the difficulty to determine regions where motion can be 1 accurately approximated by a parametric motion model. However, it has been shown that when appropriate regions are chosen, local parametric models can yield excellent performances [27,16].…”
Section: Introductionmentioning
confidence: 99%